2009
DOI: 10.1007/dcr.0b013e3181afbdaf
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Placenta Growth Factor Level Is a Prognostic Biomarker in Colorectal Cancer

Abstract: Preoperative serum placenta growth factor levels were higher in patients with colorectal cancer, were negatively correlated with the serum sFlt-1, and could be used as a prognostic indicator for recurrence and survival for colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 29 publications
5
26
1
Order By: Relevance
“…Results linked high circulating PlGF to adverse prognosis in renal (Matsumoto et al 2003) and oral squamous cell carcinoma (Cheng et al 2012) but not in hepatocellular cancer (Nagaoka et al 2010), and high preoperative PlGF levels predicted reduced recurrence-free and overall survival in colorectal cancer patients undergoing curative surgery (Wei et al 2009, Rahbari et al 2011. The latter data fit with our observation that PlGF levels O50th percentile correlated with shorter TTP in the prospective intestinal NET cohort.…”
Section: Discussionsupporting
confidence: 81%
“…Results linked high circulating PlGF to adverse prognosis in renal (Matsumoto et al 2003) and oral squamous cell carcinoma (Cheng et al 2012) but not in hepatocellular cancer (Nagaoka et al 2010), and high preoperative PlGF levels predicted reduced recurrence-free and overall survival in colorectal cancer patients undergoing curative surgery (Wei et al 2009, Rahbari et al 2011. The latter data fit with our observation that PlGF levels O50th percentile correlated with shorter TTP in the prospective intestinal NET cohort.…”
Section: Discussionsupporting
confidence: 81%
“…These downstream gene protein products, which in clude VEGF, stromal cell-derived factor 1α (SDF-1α) and PlGF, promote cell survival under hypoxic conditions. Among patients with colorectal cancer, expression of these 4 AMs has been shown to correlate with rates of lymph node or liver metastasis, disease-free survival, and overall survival (17)(18)(19)(20). However, the effects of pre-operative treatment on expression of AMs in rectal cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…PlGF stimulates the proliferation of endothelial cells and indirectly upregulates the expression of various proangiogenic factors including VEGFA, FGF2, and PDGFB (29). Previous reports suggested that plasma PlGF levels are upregulated and correlated with survival in various cancers (12)(13)(14). Surprisingly, serum PlGF was found to be more useful than VEGFA in predicting worse prognostic features and survival in patients with operable gastric cancer (14) and hepatocellular cancer (30).…”
Section: Discussionmentioning
confidence: 99%